Kopi Arabika Sebagai Ide Penciptaan Karya Seni Grafis - Septian Pebin Putra; Rajudin Rajudin; Elvis Elvis (Institut Seni Indonesia Padang Panjang, 2023)
ABSTRACTThis article discusses the creation of five graphic artworks that use Arabica coffee as a creative subject. The reason for choosing Arabica coffee as the main subject is because it is extensively cultivated in the Kerinci region. Additionally, Arabica coffee fruits have diverse and attractive shapes and colors, such as light green, dark green, yellow, and red. Arabica coffee is transformed into graphic artworks by combining the techniques of hardboardcut and stencil. A representational form is the approach used in the creation of these artworks. The concepts of distortion and disformation are applied in shaping the artworks. The result of this creation is five graphic artworks titled